Actinobacteria Associated With Arbuscular Mycorrhizal Funneliformis mosseae Spores, Taxonomic Characterization and Their Beneficial Traits to Plants: Evidence Obtained From Mung Bean (Vigna radiata) and Thai Jasmine Rice (Oryza sativa) - Lasudee, Krisana; Tokuyama, Shinji; Lumyong, Saisamorn; Pathom-aree, Wasu (Frontiers in Microbiology, 2018)
In this study, we report on the isolation of actinobacteria obtained from spores of Funneliformis mosseae and provide evidence for their potential in agricultural uses as plant growth promoters in vitro and in vivo. Actinobacteria were isolated from spores of F. mosseae using the dilution plate technique and media designed for the selective isolation of members of specific actinobacterial taxa. Six strains namely 48, S1, S3, S4, S4-1 and SP, were isolated and identified based on16S rRNA gene sequences. Phylogenetic analysis showed that isolate SP belonged to the genus Pseudonocardia with P. nantongensis KLBMP 1282T as its closest neighbor. The remaining isolates belonged to the genus Streptomyces. Two isolates, 48 and S3 were most closely related to S. thermocarboxydus DSM 44293T. Isolates S4 and S4-1 shared the highest 16S RNA gene similarity with S. pilosus NBRC 127772T. Isolate S1 showed its closest relationship with the type strain of S. spinoverrucosus NBRC14228T. The ability of these isolates to produce indole-3-acetic acid (IAA), siderophores and the ability to solubilize phosphate in vitro were examined. All isolates produced siderophores, four isolates produced IAA and two isolates solubilized inorganic phosphate at varying levels. S. thermocarboxydus isolate S3 showed the highest IAA production with high activities of phosphate solubilization and siderophore production. The inoculation of mung beans (Vigna radiata) with this strain resulted in a significant increase in fresh weight, root length and total length as an effect of IAA production. In an experiment with rice (Oryza sativa), S. thermocarboxydus isolate S3 promoted the growth of rice plants grown in low nutritional soil under induced drought stress. This report supports the view that the inoculation of rice with plant growth promoting actinobacteria mitigates some adverse effects of low nutrient and drought stress on rice.